Design and Synthesis of Selective Acetylcholinesterase Inhibitors: Arylisoxazole‐Phenylpiperazine Derivatives. Issue 2 (30th January 2019) - Saeedi, Mina; Mohtadi‐Haghighi, Dorrin; Mirfazli, Seyedeh Sara; Mahdavi, Mohammad; Hariri, Roshanak; Lotfian, Hania; Edraki, Najmeh; Iraji, Aida; Firuzi, Omidreza; Akbarzadeh, Tahmineh
Abstract: In this work, a novel series of arylisoxazole‐phenylpiperazines were designed, synthesized, and evaluated toward acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). Our results revealed that [5‐(2‐chlorophenyl)‐1, 2‐oxazol‐3‐yl](4‐phenylpiperazin‐1‐yl)methanone (5c ) was the most potent AChE inhibitor with IC50 of 21.85 μm . It should be noted that most of synthesized compounds showed no BChE inhibitory activity and [5‐(2‐fluorophenyl)‐1, 2‐oxazol‐3‐yl](4‐phenylpiperazin‐1‐yl)methanone (5a ) was the most active anti‐BChE derivative (IC50 =51.66 μm ). Also, kinetic studies for the AChE and BChE inhibitory activity of compounds5c and5a confirmed that they have simultaneously bound to the catalytic site (CS) and peripheral anionic site (PAS) of both AChE and BChE. Furthermore, docking study of compound5c showed desired interactions of that compound with amino acid residues located in the active and peripheral anionic sites. Compound5c was also evaluated for its BACE1 inhibitory activity and demonstrated IC50 =76.78 μm . Finally, neuroprotectivity of compound5c on Aβ‐treated neurotoxicity in PC12 cells depicted low activity. Abstract :